2020
DOI: 10.1186/s13011-020-00315-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with different forms of alcohol use behaviors among college students in Bhutan: a cross-sectional study

Abstract: Background Alcohol use has impacts on several dimensions of health, including physical health and mental health, particularly in college-age populations. Therefore, this study aimed to estimate the prevalence and to determine factors associated with alcohol use behaviors among college students in Bhutan. Methods A cross-sectional design was applied to collect data from the participants. A simple random method was used to select the participants from the lists of students who were attending the four selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…One of the reasons why Malaysian university students smoke is due to stress (36) as seen in this study, 57.1% students reported as having stress sometimes. Previous study reported that a tobacco-using person were more prone to binge drinking than nontobacco-using person (37). A study done among French college students reported that majority of the participants also having high level of perceived stress (86.3%) and psychological distress (79.3%) that linked to low self-esteem, selection of fields and freedom of schedule organization (38).…”
Section: Discussionmentioning
confidence: 95%
“…One of the reasons why Malaysian university students smoke is due to stress (36) as seen in this study, 57.1% students reported as having stress sometimes. Previous study reported that a tobacco-using person were more prone to binge drinking than nontobacco-using person (37). A study done among French college students reported that majority of the participants also having high level of perceived stress (86.3%) and psychological distress (79.3%) that linked to low self-esteem, selection of fields and freedom of schedule organization (38).…”
Section: Discussionmentioning
confidence: 95%
“…Uganda, in particular, faces significant challenges related to alcohol consumption, with exceedingly high rates compared to the global average [8][9]. The cultural acceptance and economic importance of alcohol in Uganda contribute to its widespread use, making it a pertinent public health concern [11][12][13]. Studies indicate a concerning trend of early alcohol initiation among adolescents and young adults in Uganda, emphasizing the need for targeted interventions to address this issue [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…5 As a result, Bhutan has been recording many deaths from alcohol use and dependence for many years. 6 People with alcohol use disorders (PwAUDs) experience recurrent or persistent social, interpersonal, personal, academic, or occupational problems. 7 The Royal Government of Bhutan with the help of the United Nations Office on Drugs and Crime had come up with a long-term medical intervention to treat alcohol dependence.…”
Section: Introductionmentioning
confidence: 99%